Adaptive Behavior of Dynamic Orthoester Cryptands - Shyshov, Oleksandr; Brachvogel, Rene-Chris; Bachmann, Tobias; Srikantharajah, Rubitha; Segets, Doris; Hampel, Frank; Puchta, Ralph; Von Delius, Max (Angewandte Chemie International Edition, 2017)
The integration of dynamic covalent bonds into macrocycles has been a tremendously successful strategy for investigating noncovalent interactions and identifying effective host–guest pairs. While numerous studies have focused on the dynamic responses of macrocycles and larger cages to various guests, the corresponding constitutionally dynamic chemistry of cryptands remains unexplored. Reported here is that cryptands based on orthoester bridgeheads offer an elegant entry to experiments in which a metal ion selects its preferred host from a dynamic mixture of competing subcomponents. In such dynamic mixtures, the alkali metal ions Li+, Na+, K+, Rb+, and Cs+ exhibit pronounced preferences for the formation of cryptands of certain sizes and donor numbers, and the selection is rationalized by DFT calculations. Reported is also the first self-assembly of a chiral orthoester cryptate and a preliminary study on the use of stereoisomers as subcomponents.
Keywords: cryptands; dynamic combinatorial chemistry; supramolecular chemistry; host–guest chemistry; NMR spectroscopy

Red Light Triggered Fluorogenic Reaction with Picomolar Sensitivity Toward Nucleic Acids - Zozulia, Oleksii; Bachmann, Tobias; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
We have previously reported on a red light triggered, singlet oxygen-mediated fluorogenic reaction that is templated in a highly sequence specific fashion by nucleic acids (S. Dutta, A. Fulop, A. Mokhir, Bioconjgate Chem.2013, 24 (9), 1533-1542). Up to the present date, it has remained a single templated reaction responsive to nontoxic >650 nm light. However, it is operative only in the presence of relatively high (>2 nM) concentrations of templates that dramatically limit its applicability in nucleic acid detection. In the current work, we established that an inefficient intermolecular electron transfer involved in reduction of the 1,4-endoperoxide intermediate, formed in the rate-limiting reaction step, is responsible for inhibition of the reaction at low reagent concentrations. We suggested the solution of the problem which includes a combination of a cleavable (9-alkoxyanthracene) moiety with a two-electron donating fragment in one molecule. This approach enables the efficient intramolecular electron transfer to the endoperoxide intermediate in the critical reaction step. Due to the intramolecular character of the latter process, it is practically independent of concentration of the reagents. The reaction based on the improved cleavable moiety was found to be >200-fold more sensitive than the previously reported one. It is fast, sequence specific, and compatible with live cells. Accounting for short reactions times (<30 min), nontoxic trigger (red light), excellent sensitivity, and sequence specificity, this is presently the best reported photochemical templated reaction compatible with live cells.
CRIS-Team Scopus Importer:2019-08-09

Red light-triggered nucleic acid-templated reaction based on cyclic oligonucleotide substrates - Zozulia, Oleksii; Bachmann, Tobias; Deussner-Helfmann, Nina S.; Beierlein, Frank; Heilemann, Mike; Mokhir, Andriy (Chemical Communications, 2019)
A red light-triggered reaction based on cyclic oligonucleotide substrates that is accelerated over 30-fold by specific nucleic acid templates and generates a bright fluorescent probe was developed. We confirmed that this reaction is compatible with fluorescence correlation spectroscopy (FCS) thereby allowing detection of nucleic acids down to 1 nM.
CRIS-Team Scopus Importer:2019-09-17